E-112 A single center comparison of stroke treatment times: impact of a mobile stroke unit. (22nd July 2018) - Shownkeen, H; Mohajer-Esfahani, M; Crumlett, H; Lindstrom, A
Abstract : Background: Stroke is the 5th leading cause of death in the United States today according to the American Stroke Association (2014). Acute stroke treatment is time sensitive in nature and the faster symptoms are identified and treated the lower the likelihood of disability. The stroke treatment efficacy improves when initiated in the golden hour (Saver et al ., 2010). The ongoing issue has been getting patients to present earlier for treatment. The Mobile Stroke Unit (MSU) brings evaluation and treatment to the patients leading to potential decrease in treatment times. Methods: The mobile stroke unit responded to a six-town area within the hospital's Emergency Medical Services (EMS) system, combined population of 7 71 606. Data from mobile stroke unit patients was compared to data from stroke patients brought to the Emergency Department by conventional EMS and patients who walked into the Emergency Department (ED) from January 2017-January 2018. The MSU was dispatched for patients deemed as potential strokes by the centralized 911 dispatch. The patient was then evaluated by a specially-trained crew consisting of a critical care paramedic and a critical care nurse. Neurology evaluation occurred via telemedicine. The mobile stroke unit is equipped with IV alteplase and computerized tomography (CT). Data was collected using EMS EMR and imported to stroke database. Inclusion criteria included: 18 years or older, receive treatment in mobile stroke unit or emergency department, treated with IV alteplase. Results: Analysis of last known well to CT complete demonstrated patients treated on the MSU (73 min, n=18) received a non-contrast head CT 30 min faster compared to EMS patients (103 min, n=17) arriving at the ED. The CT scans were resulted 31 min faster in the MSU patient population (79 min, n=18) compared to EMS patients (110 min, n=17). Overall, a 39 min decrease in time to treatment was seen for patients treated by the MSU (97 min, n=18) compared to patients arrived to the ED via EMS (136 min, n=17). Of patients who received IV alteplase, 27% of from MSU were treated within 60 min of last known well compared to 6% coming to the ED via EMS. Conclusions: Patients treated in the mobile stroke unit demonstrate a decrease in time to treatment. This is most significant in treating patients within 60 min of the last known well, the golden hour of stroke treatment. Data is not statistically significant at this time due to small sample size; however, the data is encouraging and should continue to be studied. In conclusion, the use of a mobile stroke unit provides a time to treatment benefit. Disclosures: H. Shownkeen: None. M. Mohajer-Esfahani: None. H. Crumlett: None. A. Lindstrom: None.